2018
DOI: 10.1002/biof.1455
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid promotes cell cycle arrest and decreases proliferation through WNT/β‐catenin modulation in colorectal cancer cells exposed to γ‐radiation

Abstract: The effects of radiation are known to be potentiated by N‐3 polyunsaturated fatty acids, which modulate several signaling pathways, but the molecular mechanisms through which these fatty acids enhance the anticancer effects of irradiation in colorectal cancer (CRC) treatment remain poorly elucidated. Here, we aimed to ascertain whether the fatty acid docosahexaenoic acid (DHA) exerts a modulating effect on the response elicited by radiation treatment (RT). Two CRC cell lines, Caco‐2 and HT‐29, were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Inhibition of proliferation by DHA in MCF-7 cells via pAKT signalling was found in another study [226]. DHA decreased the viability of HT-29 and CaCo-2 colorectal cancer cells and enhanced the effect of irradiation; the underlying mechanism involved the WNT/beta-catenin pathway [227]. Ω-3 PUFAs, particularly DHA, also modulated angiogenesis via miR-126 methylation and VEGF expression in HCT-116 and Caco-2 cells [228].…”
Section: ω-3 Pufasmentioning
confidence: 77%
“…Inhibition of proliferation by DHA in MCF-7 cells via pAKT signalling was found in another study [226]. DHA decreased the viability of HT-29 and CaCo-2 colorectal cancer cells and enhanced the effect of irradiation; the underlying mechanism involved the WNT/beta-catenin pathway [227]. Ω-3 PUFAs, particularly DHA, also modulated angiogenesis via miR-126 methylation and VEGF expression in HCT-116 and Caco-2 cells [228].…”
Section: ω-3 Pufasmentioning
confidence: 77%
“…DHA has shown anticancer effects in several types of cancers [15,16,17]. The mechanisms underlying the anticancer effect of DHA reportedly include regulation of Wnt/β-catenin inhibition [18], oxidative DNA damage [19], and mitogen-activated protein kinase activation [14]. Furthermore, our previous studies have revealed that DHA induces autophagy whilst suppressing mTOR in human cervical cancer, prostate cancer, lung cancer, and glioblastoma cells [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Docosahexaenoic acid is a major n-3 PUFA involved in anticancer activity. In vitro studies have demonstrated that docosahexaenoic acid inhibits cancer cell proliferation and resistance to irradiation by regulating the Akt and Wnt pathways [ 180 , 181 ]. Docosahexaenoic acid alleviates cancer aggressiveness by modulating the STAT3/nuclear factor kappa B (NF-kB) axis and M2 macrophage polarization [ 182 , 183 ].…”
Section: Dietary Lipids and Cancermentioning
confidence: 99%